Pengaruh Kompetensi dan Disiplin Kerja terhadap Produktivitas Kerja Karyawan PT Lion Wings Jakarta Timur - Siti Wahyuni; Muhammad Harri; Muhammad Kausar Maulana (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2026)
The purpose to analyze the influence of competence and work discipline on employee work productivity at PT Lion Wings Jakarta Timur. This research is included in the category of causal associative research using a quantitative approach. The population in this study Were employees of PT Lion Wings Jakarta Timur. Using the Slovin formula, the sample in this study. The technique used for sampling is simple random sampling. The analytical method uses simultaneous and partially linear regression analysis. The results of the research show that in simultaneous and partially ways competence and work discipline have a positive and significant effect on employee work productivity at PT Lion Wings Jakarta Timur.